Strengthening Local Wisdom in Coastal Climate Resilience in Southeast Asia - Aspan, Zulkifli; Jundiani; Irwansyah; Ji Hyun Park; Wildan Azkal Fikri (International Law Discourse in Southeast Asia, 2025)
The resilience of coastal communities in the Global South, including in Southeast Asia, in facing the impacts of climate change requires a responsive and adaptive environmental legal framework. Local wisdom serves as a strategic element in safeguarding the rights of coastal communities and enhancing their capacity to withstand environmental threats. This study examines how integrating local wisdom into environmental law can contribute to strengthening coastal climate resilience, particularly within the context of Indonesia and comparable jurisdictions in Asia. Employing normative legal research, this study adopts conceptual, legislative, and comparative approaches to highlight best practices and theoretical reflections. The findings demonstrate that policies recognizing and incorporating local knowledge into environmental law hold significant potential to support effective adaptation and mitigation efforts in coastal areas. Comparative analysis of policies across different countries in the region shows that embracing local wisdom can foster a more context-sensitive and sustainable legal framework. Accordingly, this study proposes that legal frameworks in developing countries should integrate local wisdom as an integral element of environmental law reform to strengthen the resilience of vulnerable coastal communities. The implications suggest that such integration is not only relevant for climate change adaptation but also for building more responsive, participatory, and effective environmental governance in the developing world.